Pengaruh Good Corporate Governance, Karakteristik Perusahaan, Dan Struktur Kepemilikan Terhadap Pengungkapan Sustainability Report: Suatu Studi Literatur - Nevis Hezmita; Trinandari Prasetya Nugrahanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study is a literature review that aims to analyze the factors that conceal the disclosure of sustainability reports in Indonesia by reviewing seven related empirical journals. The most frequently studied variables include good corporate governance (GCG) mechanisms such as the size and independence of the board of commissioners, audit committee, board of directors, and the existence of a governance committee, in addition to company characteristics such as profitability, leverage, company size, liquidity, ownership structure, and external audit quality. The results of the review indicate that most studies prove that company size and profitability have a positive effect on the disclosure of sustainability reports. The role of GCG also shows mixed results, where board independence, institutional ownership, and external audit quality in some studies have a positive effect.